ICT and creativity in architecture teaching - Alba-Dorado, María Isabel (My University, 2020)
The purpose of this paper is to disseminate the results of an educational innovation project developed at the School of Architecture of the University of Malaga entitled “Information and Communication Technologies (ICT) as support for the development and promotion of creative thinking processes in university teaching”. This project, in which professors from various areas of knowledge have participated, has deepened in the maximum use of the opportunities that these resources provide not only for the achievement of pedagogical objectives, but also to encourage, stimulate and develop creative thinking, Critical and innovative. The results have shown that the use of ICT in architecture teaching encourages creativity in students and allows the development of a proactive approach to creativity in the classroom by exercising skills related to creative thinking and creative behavior in students.
Keywords: Arquitectura; Architectural projects; ICT tools; Critical discipline; Experimental pedagogy